The Effects of Electrocautery on Peripheral Nerve: An Experimental Study - Karalezli, Nazim; Koktekir, Ender; Yildirim, Serhat; Toy, Hatice; Oz, Mehmet; Yuceturk, Aydin (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Background The aim of this study was to assess the usability of an electrocautery device as nerve stimulator and to investigate histopathologically the adverse effects of electrocautery at low power on rat sciatic nerves.Methods A total of 36 female Sprague-Dawley albino rats were divided into six groups according to the power applied to their sciatic nerves (1, 2, 3, 4, 5 and 6 W, respectively). Pathologic changes were studied by microscopic examination and scored (no change = 0, mild = 1, moderate = 2, severe = 3). Multiple comparisons were provided for all groups by the Bonferroni test (one-way analysis of variance). A p value < 0.05 was accepted as statistically significant.Results The average scores were 2.66 ± 0.51, 3.66 ± 0.51, 5.83 ± 1.83, 10.0 ± 1.78, 11.0 ± 1.54, and 13.8 ± 0.89 in groups 1 to 6, respectively. Significant differences were found between all groups (p < 0.01), except between groups 1 and 2, groups 2 and 3, and groups 4 and 5 (p > 0.05) Variable motor responses and foot deformities were observed at the different power levels.Conclusion Although electrocautery devices provoke motor responses if getting in contact with peripheral nerves as do nerve stimulators, their use induces histopathologically adverse effects even at the lowest power. Their use around peripheral nerves should be avoided.
Keywords: electrocautery; nerve; stimulation